(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
The following study shows that Krashen's five hypotheses are the acquisition-learning hypothesis, the monitor hypothesis and the affective filter hypothesis in second language acquisition. These are analyzed in two different students.